Genomics and epidemiology of the P.1 SARS-CoV-2 lineage in Manaus, Brazil - Faria, NR; Mellan, TA; Whittaker, C; Claro, IM; Candido, DDS; Mishra, S; Crispim, MAE; Sales, FCS; Hawryluk, I; McCrone, JT; Hulswit, RJG; Franco, LAM; et al. (American Association for the Advancement of Science, 2021)
Cases of SARS-CoV-2 infection in Manaus, Brazil, resurged in late 2020, despite previously high levels of infection. Genome sequencing of viruses sampled in Manaus between November 2020 and January 2021 revealed the emergence and circulation of a novel SARS-CoV-2 variant of concern. Lineage P.1, acquired 17 mutations, including a trio in the spike protein (K417T, E484K and N501Y) associated with increased binding to the human ACE2 receptor. Molecular clock analysis shows that P.1 emergence occurred around mid-November 2020 and was preceded by a period of faster molecular evolution. Using a two-category dynamical model that integrates genomic and mortality data, we estimate that P.1 may be 1.7-2.4-fold more transmissible, and that previous (non-P.1) infection provides 54-79% of the protection against infection with P.1 that it provides against non-P.1 lineages. Enhanced global genomic surveillance of variants of concern, which may exhibit increased transmissibility and/or immune evasion, is critical to accelerate pandemic responsiveness.